2009
DOI: 10.1164/rccm.200901-0023oc
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar Macrophage Dysregulation in Hermansky-Pudlak Syndrome Type 1

Abstract: In HPS-1, alveolar inflammation predominantly involves macrophages and is associated with high lung concentrations of cytokines and chemokines. HPS-1 alveolar macrophages provide a model system in which to study the pathogenesis and treatment of HPS pulmonary fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
72
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 64 publications
(79 citation statements)
references
References 52 publications
(62 reference statements)
7
72
0
Order By: Relevance
“…Furthermore, alveolar inflammation precedes lung remodeling, consisting of both airspace enlargement and subsequent collagen deposition (8). Our longitudinal survey demonstrated that alveolitis began much earlier than previously suggested by BAL studies in both HPS mouse models carrying single mutations, and adult patients with HPS1 (14,34,35). These data provide strong support for a more comprehensive evaluation of the pediatric HPS population, and suggest that earlier treatment protocols (before the development of clinically apparent restrictive lung disease) may be important in modifying the disease course.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Furthermore, alveolar inflammation precedes lung remodeling, consisting of both airspace enlargement and subsequent collagen deposition (8). Our longitudinal survey demonstrated that alveolitis began much earlier than previously suggested by BAL studies in both HPS mouse models carrying single mutations, and adult patients with HPS1 (14,34,35). These data provide strong support for a more comprehensive evaluation of the pediatric HPS population, and suggest that earlier treatment protocols (before the development of clinically apparent restrictive lung disease) may be important in modifying the disease course.…”
Section: Discussionmentioning
confidence: 50%
“…As previously described (14), subjects with HPS1 and healthy research volunteers were evaluated at the National Institutes of Health Clinical Center (Bethesda, MD) and were enrolled in protocols 95-HG-0193 and/ or 04-H-0211, which were approved by the Institutional Review Boards of the National Human Genome Research Institute (Bethesda, MD).…”
Section: Samples and Data From Patients With Hpsmentioning
confidence: 99%
“…First, there is strong evidence that macrophage-mediated inflammation precedes pulmonary fibrosis in patients with HPS. Bronchoalveolar lavage fluid of patients with HPS-PF contained increased total cell counts and alveolar macrophages (35), at a time when patients still had relatively preserved lung function. Furthermore, alveolar macrophages from patients with HPS have been shown to be constitutively activated, expressing excess cytokines and chemokines when studied ex vivo (35).…”
Section: Pulmonary Fibrosis: Pathogenesismentioning
confidence: 94%
“…Interestingly, ex vivo, pirfenidone showed significantly decreased inflammatory cytokines in the alveolar macrophages of patients with HPS (35). An initial clinical trial of pirfenidone in patients with HPS-1 showed no significant slowing of fibrosis progression by serial measurement of FVC (32).…”
Section: Clinical Management Of Pulmonary Fibrosismentioning
confidence: 98%
See 1 more Smart Citation